2007
DOI: 10.1128/mcb.00787-07
|View full text |Cite
|
Sign up to set email alerts
|

The Slx5-Slx8 Complex Affects Sumoylation of DNA Repair Proteins and Negatively Regulates Recombination

Abstract: Recombination is important for repairing DNA lesions, yet it can also lead to genomic rearrangements. This process must be regulated, and recently, sumoylation-mediated mechanisms were found to inhibit Rad51-dependent recombination. Here, we report that the absence of the Slx5-Slx8 complex, a newly identified player in the SUMO (small ubiquitin-like modifier) pathway, led to increased Rad51-dependent and Rad51-independent recombination. The increases were most striking during S phase, suggesting an accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
188
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(197 citation statements)
references
References 51 publications
9
188
0
Order By: Relevance
“…Moreover, SUMO is implicated in the maintenance of rDNA stability by suppressing illegitimate recombination among the yeast rDNA repeats [22]. Consistent with this widespread effect on genomic integrity, it was found that many other proteins involved in DNA repair are sumoylated, notably PCNA, Rad52, Rfa1, Rfa2, Sgs1 helicase, as well as its human homologues, BLM and WRN [23][24][25][26][27][28]. Many of these proteins are found either transiently or stably associated with PML-NBs in mammalian cells in response to DNA damage (reviewed in [20]).…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…Moreover, SUMO is implicated in the maintenance of rDNA stability by suppressing illegitimate recombination among the yeast rDNA repeats [22]. Consistent with this widespread effect on genomic integrity, it was found that many other proteins involved in DNA repair are sumoylated, notably PCNA, Rad52, Rfa1, Rfa2, Sgs1 helicase, as well as its human homologues, BLM and WRN [23][24][25][26][27][28]. Many of these proteins are found either transiently or stably associated with PML-NBs in mammalian cells in response to DNA damage (reviewed in [20]).…”
Section: Introductionmentioning
confidence: 60%
“…Mutations in genes involved in the SUMO pathway, such as Ubc9, Mms21, Ulp1, Slx5 and Slx8, render cells sensitive to DNA damage, and many proteins involved in the maintenance of genome stability have been shown to become sumoylated during the damage response [23][24][25][26][27][28]. Specifically, it has been shown that the SUMO pathway plays an important role in homologous recombination and the resumption of stalled/collapsed replication forks [27,[36][37][38].…”
Section: Dna Repair and Sumo In Yeastmentioning
confidence: 99%
See 2 more Smart Citations
“…55 This is associated with an increase in the number and duration of Rad52 foci during S-phase, suggesting that Slx5/8 may act to suppress damage that occurs during replication and to channel that damage into faster repair pathways. The relevant substrates for Slx5/8 are not currently known, though it has been suggested that they may target the degradation of proteins involved in Rad51-independent recombination pathways.…”
Section: Introductionmentioning
confidence: 99%